2022
DOI: 10.3390/nu14153115
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyphenols on Kidney Disease: Targeting Mitochondria

Abstract: Mitochondrial function, including oxidative phosphorylation (OXPHOS), mitochondrial biogenesis, and mitochondria dynamics, are essential for the maintenance of renal health. Through modulation of mitochondrial function, the kidneys are able to sustain or recover acute kidney injury (AKI), chronic kidney disease (CKD), nephrotoxicity, nephropathy, and ischemia perfusion. Therapeutic improvement in mitochondrial function in the kidneys is related to the regulation of adenosine triphosphate (ATP) production, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 233 publications
1
20
0
Order By: Relevance
“…Antioxidants, vitamins, and minerals were also demonstrated to prevent gentamicin-induced nephrotoxicity [ 108 ]. In an experimental study, strong antioxidant and nephroprotective activity were revealed for polyphenols (caffeic acid phenethyl ester, curcumin, quercetin, resveratrol, catechin, hesperidin, and ellagic acid [ 109 ]). There was also specific nephroprotective treatment when some nephrotoxic drugs were administered in an experimental study: cilastatin administration, a blocker of megalin receptors and inhibitor of dehydropeptidase-1, reduced nephrotoxicity associated with vancomycin and aminoglycosides.…”
Section: Preventive Factors Of Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…Antioxidants, vitamins, and minerals were also demonstrated to prevent gentamicin-induced nephrotoxicity [ 108 ]. In an experimental study, strong antioxidant and nephroprotective activity were revealed for polyphenols (caffeic acid phenethyl ester, curcumin, quercetin, resveratrol, catechin, hesperidin, and ellagic acid [ 109 ]). There was also specific nephroprotective treatment when some nephrotoxic drugs were administered in an experimental study: cilastatin administration, a blocker of megalin receptors and inhibitor of dehydropeptidase-1, reduced nephrotoxicity associated with vancomycin and aminoglycosides.…”
Section: Preventive Factors Of Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…GSPE, a natural bioactive compound from plant, exhibits great therapeutic properties through inhibiting oxidative stress and promoting mitochondrial biogenesis ( Ashkar et al, 2022 ). Researches show in streptozotocin-and high-carbohydrate/high-fat diet-induced diabetic rats, GSPE treatment is able to enhance mitochondrial biogenesis, and ameliorate podocyte injury and apoptosis via AMPK-Sirtuin-1-PGC-1α-TFAM signaling pathway ( Bao et al, 2014 ).…”
Section: Natural Products For Regulating Mitochondrial Functionmentioning
confidence: 99%
“…Hesperetin, a natural bioactive phytochemical from citrus plants, exhibits wide pharmacological therapeutic effects on cancer, cardiovascular diseases and diabetes ( Chen et al, 2019b ; Ashkar et al, 2022 ). Hesperetin also shows renal protective effects by its anti-oxidative properties ( Ashkar et al, 2022 ). Hesperetin can activate Nrf2-ARE signaling pathway via increasing Nrf2 and p-Nrf2 levels in kidney tissue ( Chen et al, 2019b ).…”
Section: Natural Products For Regulating Mitochondrial Functionmentioning
confidence: 99%
See 2 more Smart Citations